Experience and Appreciation of Health Care Teams Regarding a New Model of Pharmaceutical Care in Long-Term Care Settings. Issue 3 (8th September 2022) - Turcotte, Véronique; Kröger, Edeltraut; Rouleau, Rachel; Durand, Étienne; Poirier, Karine; Guénette, Line
Abstract: In long-term care (LTC) homes, the management of frail older residents' pharmacotherapy may be challenging for health care teams. A new pharmaceutical care model highlighting the recently expanded scope of pharmacists' practice in Quebec, Canada, was implemented in two LTC homes. This study aimed to evaluate health care providers' experience and satisfaction with this new practice model. Twenty-three semi-structured interviews were performed and analyzed thematically. Positive results of the model have been identified, such as increased timeliness of interventions. Barriers were encountered, such as lack of clarity regarding roles, and suboptimal communication. The increased involvement of pharmacists was perceived as useful in the context of scarce medical resources. Although requiring time and adjustments from health care teams, the new model seems to contribute to the health care providers' work satisfaction and to positively influence the timeliness and quality of care offered to LTC residents.